Silicate-based bioceramic scaffolds for dual-lineage regeneration of osteochondral defect. (February 2019) - Bunpetch, Varitsara; Zhang, Xiaoan; Li, Tian; Lin, Junxin; Maswikiti, Ewetse Paul; Wu, Yan; Cai, Dandan; Li, Jun; Zhang, Shufang; Wu, Chengtie; Ouyang, Hongwei
Abstract: Osteochondral defects are most commonly characterized by damages to both cartilage and bone tissues as a result of serious traumas or physical diseases; because these two tissues have their own unique biological properties, developing a single monophasic scaffold that can concurrently regenerate these two specific lineages becomes a challenge. To address this concern, a silicon-based bioceramic (SiCP) scaffold was fabricated. The efficiency and underlying mechanisms of SiCP for osteochondral defect regeneration were investigated. At 8 and 16 weeks post-implantation in a rabbit model of osteochondral defect, gross morphology, histological, and micro-CT images showed that SiCP scaffolds distinctly promoted subchondral bone and cartilage regeneration when compared to calcium-phosphate based bioceramics (CP) scaffolds without silicon. In vitro, SiCP was also shown to promote bone marrow stem cells (BMSC) osteogenesis ( ALP, RUNX2, OCN ) and help maintain chondrocytes phenotype ( Acan, Sox9, Col2a1 ), validated by qPCR, western blot, and RNA-sequencing (RNA-seq). Additionally, the descriptive analysis of RNA-seq using Gene Ontology (GO) and KEGG pathway analysis revealed biological processes related to cartilage and bone development and extracellular matrices in chondrocytes, as well as related to early osteogenesis in BMSC, indicating that Si ions play an important role in the regeneration of both tissues. Conclusively, the development of silicon-based bioceramic scaffolds may be a promising approach for osteochondral defect regeneration due to their unique dual-lineage bioactivity.